Developing Framework for South African Airlines’ Growth in the Era of Advanced Digitalisation - Aigbavboa, Clinton; Mkhize, Nompumelelo; Nagapan, Sasitharan; Ebekozien, Andrew; Salman, Ahmad (Journal of Posthumanism, 2025)
This study identified 4IR roles and developed a framework for the airlines’ growth in the era of advanced digitalisation. The study adopted a qualitative method and engaged 56 experts in face-to-face interviews to achieve the aim. The participants were South African Civil Aviation Authority and Tourism industry staffers, top staffers of state-owned airlines, and selected passengers. The research utilised a thematic approach to analyse the collated face-to-face data. Findings show that most 4IR technologies can be useful to enhance airlines’ growth in South Africa. Also, 4IR technologies can be used to improve the key components of airlines’ growth framework (government factors, airline factors, sector competition, and strategic alliance) in South Africa. Besides using the suggested framework as a guideline to improve profitability, competitiveness, and airline sustainability, the study is encouraging airlines operators and other key stakeholders to improve their digitalisation operations.